A reflection on scientific publications - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Publishing scientific articles constitutes an important sign of scientific individual and institutional production in the professional context. Two documents, one related to the current situation of publications in Cuba, and another one which represents a Ministry Strategy to increase the quality of biol-medical journals have given place to this reflection. As main ideas which complement the already identified ones, it is stated the need of improving qualitatively and quantitatively the scientific production  in the health area and in particular at the base of the system, due to the close relationship between research-publication, so as to promote in medical professionals an adequate writing competence.